2017
DOI: 10.1098/rsos.160923
|View full text |Cite
|
Sign up to set email alerts
|

Robust associations between the 20-item prosopagnosia index and the Cambridge Face Memory Test in the general population

Abstract: Developmental prosopagnosia (DP) is a neurodevelopmental condition, characterized by lifelong face recognition deficits. Leading research groups diagnose the condition using complementary computer-based tasks and self-report measures. In an attempt to standardize the reporting of self-report evidence, we recently developed the 20-item prosopagnosia index (PI20), a short questionnaire measure of prosopagnosic traits suitable for screening adult samples for DP. Strong correlations between scores on the PI20 and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

12
90
2
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 72 publications
(111 citation statements)
references
References 28 publications
(50 reference statements)
12
90
2
1
Order By: Relevance
“…These factors potentially explain why some individuals who meet Self-ratings of prosopagnosia severity 10 objective criteria for DP return typical scores on self-report measures (e.g. Bowles et al, 2009;Gray et al, 2017;Palermo et al, 2017). Although this did not occur in the current study (all 47 DPs scored above the recommended cut-off on the PI20), it is important to note that they had all received feedback on their face recognition skills (i.e.…”
Section: Discussionmentioning
confidence: 74%
“…These factors potentially explain why some individuals who meet Self-ratings of prosopagnosia severity 10 objective criteria for DP return typical scores on self-report measures (e.g. Bowles et al, 2009;Gray et al, 2017;Palermo et al, 2017). Although this did not occur in the current study (all 47 DPs scored above the recommended cut-off on the PI20), it is important to note that they had all received feedback on their face recognition skills (i.e.…”
Section: Discussionmentioning
confidence: 74%
“…The relationship between confidence and performance is not well understood. Evidence has shown that people's self-rated abilities with face matching and memory may be predictive of their actual abilities, although this association may only be modest (Bate & Dudfield, 2019;Bobak, Mileva, & Hancock, 2019;Bobak, Pampoulov, & Bate, 2016;Gray, Bird, & Cook, 2017;Palermo et al, 2017;Shah, Sowden, Gaule, Catmur, & Bird, 2015). However, research has shown that confidence at the level of individual responses does appear to reflect accuracy.…”
Section: Confidencementioning
confidence: 99%
“…None of the DPs had a history of brain injury or psychiatric disorder (e.g., Schizophrenia, Autism Spectrum Disorder). Diagnostic evidence for the presence of DP was collected using the Cambridge Face Memory Test (CFMT; Duchaine & Nakayama, 2006a) the Twenty-Item Prosopagnosia Index (PI20; Gray, Bird, & Cook, 2017;Shah, Gaule, Sowden, Bird, & Cook, 2015), and a Famous Face Test suitable for use with UK residents (FFT UK ). Scores on the CFMT were compared against data from 50 typical observers reported by Duchaine & Nakayama (2006a).…”
Section: Diagnostic Testingmentioning
confidence: 99%